2022
DOI: 10.1038/s41388-022-02221-0
|View full text |Cite
|
Sign up to set email alerts
|

Intratumor genetic heterogeneity and clonal evolution to decode endometrial cancer progression

Abstract: Analyzing different tumor regions by next generation sequencing allows the assessment of intratumor genetic heterogeneity (ITGH), a phenomenon that has been studied widely in some tumor types but has been less well explored in endometrial carcinoma (EC). In this study, we sought to characterize the spatial and temporal heterogeneity of 9 different ECs using whole-exome sequencing, and by performing targeted sequencing validation of the 42 primary tumor regions and 30 metastatic samples analyzed. In addition, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 102 publications
(112 reference statements)
1
17
0
Order By: Relevance
“…The high proportion of monophyletic evolution in endometrial cancer has recently been confirmed though whole exome sequencing analysis of metastases with corresponding primary tumor in a similar cohort consisting of nine endometrial cancer patients, where the majority of cases fitted into to the evolutionary model of monophyly (46). These studies found no evidence of reseeding (29,46). Interestingly, a study on metastatic prostate cancer, with survival probabilities resembling endometrial cancer, was also determined to be mainly monophyletic, while that of the more aggressive pancreatic cancer was polyphyletic.…”
Section: Monophyly Is the Dominating Evolutionary Model In Endometria...mentioning
confidence: 82%
See 3 more Smart Citations
“…The high proportion of monophyletic evolution in endometrial cancer has recently been confirmed though whole exome sequencing analysis of metastases with corresponding primary tumor in a similar cohort consisting of nine endometrial cancer patients, where the majority of cases fitted into to the evolutionary model of monophyly (46). These studies found no evidence of reseeding (29,46). Interestingly, a study on metastatic prostate cancer, with survival probabilities resembling endometrial cancer, was also determined to be mainly monophyletic, while that of the more aggressive pancreatic cancer was polyphyletic.…”
Section: Monophyly Is the Dominating Evolutionary Model In Endometria...mentioning
confidence: 82%
“…However, in the seventh case, one of the metastases was more closely related to the primary tumor than to the other metastases, a case of polyphyly, because of the presence of multiple origins (Figure 3B). The high proportion of monophyletic evolution in endometrial cancer has recently been confirmed though whole exome sequencing analysis of metastases with corresponding primary tumor in a similar cohort consisting of nine endometrial cancer patients, where the majority of cases fitted into to the evolutionary model of monophyly (46). These studies found no evidence of reseeding (29,46).…”
Section: Monophyly Is the Dominating Evolutionary Model In Endometria...mentioning
confidence: 88%
See 2 more Smart Citations
“…[18][19][20] To explain this phenomenon, it has been hypothesised that in in those patients with indolent tumour behaviour the ovarian metastases occur through fallopian tube migration at early stages of endometrial cancer progression. 21 We postulate that the model of ovarian involvement by endometrial endometrioid carcinomas portending a good prognosis can also be applied to pattern A HPVA with ovarian metastasis. To this end, we document the clinical, pathological and molecular characteristics of an institutional cohort of patients with pattern A HPVA and ovarian spread, comparing them to a group of metastatic patterns B and C HPVAs, focusing upon genomic alterations of both primary cervical tumours and their matched metastasis, as well as patient outcome.…”
Section: Introductionmentioning
confidence: 99%